Combatting fraudulent conveyance: a review of Section 96 of the Latvian Insolvency Law - Reveliņš, Mārcis (Riga Graduate School of Law, 2021)
Fraudulent conveyance is a transaction with the goal to hinder, delay or defraud creditors. One countermeasure against such behavior is provided by avoidance proceedings. In Latvia, this is available under Section 96 of the Insolvency Law. The aim of this thesis is to provide an overview of the key elements of Section 96, to highlight the existing legal challenges, and to set out specific recommendations based on international best practice, financial theory, and approach in other contexts within the Latvian legal framework. The thesis finds that in countries with stronger insolvency frameworks, the suspect periods are significantly longer than in Latvia. The thesis also concludes that the courts are relatively successful in dealing with transactions at an undervalue, however, suggests employing the NPV method in assessing transactions involving cash payments or set-offs. Finally, the thesis argues for court flexibility in determining the interested persons in relation to the debtor
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Insolvency law; Latvia